Asuhan Gizi pada Ibu dengan Mastitis - Efrizal, Wiwin (UNIVERSITAS NGUDI WALUYO, 2021)
Mastitis is an infection of the breast that generally occurs in conjunction with lactation which often occurs in nursing mothers. Blockage of the milk ducts and infection can cause mastitis. Mastitis will result in an increase in the nutritional needs of nursing mothers and disruption of the breastfeeding process so that it has an impact on the nutritional status of the baby. The purpose of writing is to provide a comprehensive description of nutritional care for mastitis mothers using the literature review method. From the study, it is known the importance of proper nutritional care for mothers with mastitis in the form of assessment, nutritional diagnosis, intervention, monitoring and evaluation as a continuous cycle to overcome mastitis problems in collaboration with the nutrition care team. The conclusion is that collaboration with other health professionals has started since the nutritional assessment was carried out, so that the management of mastitis cases can be more optimal. Abstrak Mastitis adalah infeksi pada payudara yang umumnya terjadi bersamaan dengan laktasi. Penyumbatan pada saluran ASI dan adanya infeksi dapat menimbulkan mastitis. Mastitis akan mengakibatkan meningkatkan kebutuhan gizi pada ibu menyusui dan terganggunya proses menyusui sehingga berdampak pada status gizi bayi. Asuhan gizi yang tepat pada ibu dengan mastitis dalam bentuk pengkajian, diagnosis gizi, intervensi, monitoring dan evaluasi sebagai siklus yang terus menerus dapat mengatasi masalah mastitis dengan kolaborasi bersama tim asuhan gizi. Kolaborasi dengan profesi kesehatan lainnya telah dimulai sejak pengkajian gizi dilakukan, sehingga penatalaksanaan kasus mastitis dapat lebih komprehensif.